IMPLEMENTASI P5 (PROJEK PENGUATAN PROFIL PELAJAR PANCASILA) MELALUI KEGIATAN ASISTENSI MENGAJAR - Syam, Muhammad Syaiful Amin; Erwing, Erwing; Muliana, Muliana (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2024)
This research is motivated by the challenges in optimizing the implementation of the Pancasila Student Profile Strengthening Project (P5) in elementary schools, especially in shaping students' characters. This study aims to understand the implementation of P5 through teaching assistance activities at SD Inpres Morowa. Using a qualitative approach with descriptive methods, data were collected through observation, interviews, and documentation. The research sample involved fifth grade students who were directly involved in P5. The results showed that the implementation of P5 contributed positively to the formation of students' characters, such as increasing problem-solving and collaboration skills. Environmentally friendly innovation projects, such as making tools from recycled materials, train students' creativity and awareness of the environment. The implications of these findings are opportunities for developing character-based learning, which can be a reference for other schools in implementing innovative and participatory curricula.